Pathogenesis, histopathologic findings and treatment modalities of lipoprotein glomerulopathy: A review - Eduardo Cambruzzi; Karla Lais Pêgas (Brazilian Journal of Nephrology, 2018)
Abstract Lipoprotein glomerulopathy (LPG) is an uncommon cause of nephrotic syndrome and/or kidney failure. At microscopy, LPG is characterized by the presence of lipoprotein thrombi in dilated glomerular capillaries due to different ApoE mutations. ApoE gene is located on chromosome 19q13.2, and can be identified in almost all serum lipoproteins. ApoE works as a protective factor in atherosclerosis due its interaction with receptor-mediated lipoprotein clearance and cholesterol receptor. Most common polymorphisms include ApoE2/2, ApoE3/2, ApoE3/3, ApoE4/2, ApoE4/3, and ApoE4/4. All age-groups can be affected by LPG, with a discrete male predominance. Compromised patients typically reveal dyslipidemia, type III hyperlipoproteinemia, and proteinuria. LPG treatment includes fenofibrate, antilipidemic drugs, steroids, LDL aphaeresis, plasma exchange, antiplatelet drugs, anticoagulants, urokinase, and renal transplantation. Recurrence in kidney graft suggests a pathogenic component(s) of extraglomerular humoral complex resulting from abnormal lipoprotein metabolism and presumably associated to ApoE.